2010
DOI: 10.1007/s00248-010-9710-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Diversity in Paleolithic Caves: A Study Case on the Phototrophic Biofilms of the Cave of Bats (Zuheros, Spain)

Abstract: The biological colonization of rocks in the Cave of Bats (Cueva de Los Murciélagos, Zuheros, Spain) was studied in order to reveal the diversity of microorganisms involved in the biofilm formation. The culturable, metabolically active fraction of biodeteriogens present on surfaces was investigated focusing on morphological, ultrastructural, and genetic features, and their presence related to the peculiar environmental conditions of the underground site. PCR-ITS analysis and 16S rDNA sequences were used to clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 43 publications
2
47
1
Order By: Relevance
“…Although Firmicutes (Bacillus sp) along with Escherichia coli and Staphylococcus have been considered as indicators of human impact on caves (Lavoie & Northup, 2006), their detection in the community profiles of all the caves suggested that they were indigenous to these caves. Bacillus sp have been isolated in caves (Fernandez-Cortes et al, 2011;Urzì et al, 2010) and their dispersal throughout the cave ecosystem is enhanced by their abilities to produce spores. Phylogenetic trees of other DGGE sequences showed that these can be grouped under Acidobacteria, Actinobacteria and Proteobacteria and similar groups have also been detected on cave walls (Schabereiter-Gurtner et al, 2002;Ikner et al, 2007;Urzì et al, 2010).…”
Section: Culture Independent and Dependent Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Although Firmicutes (Bacillus sp) along with Escherichia coli and Staphylococcus have been considered as indicators of human impact on caves (Lavoie & Northup, 2006), their detection in the community profiles of all the caves suggested that they were indigenous to these caves. Bacillus sp have been isolated in caves (Fernandez-Cortes et al, 2011;Urzì et al, 2010) and their dispersal throughout the cave ecosystem is enhanced by their abilities to produce spores. Phylogenetic trees of other DGGE sequences showed that these can be grouped under Acidobacteria, Actinobacteria and Proteobacteria and similar groups have also been detected on cave walls (Schabereiter-Gurtner et al, 2002;Ikner et al, 2007;Urzì et al, 2010).…”
Section: Culture Independent and Dependent Surveymentioning
confidence: 99%
“…Bacillus sp have been isolated in caves (Fernandez-Cortes et al, 2011;Urzì et al, 2010) and their dispersal throughout the cave ecosystem is enhanced by their abilities to produce spores. Phylogenetic trees of other DGGE sequences showed that these can be grouped under Acidobacteria, Actinobacteria and Proteobacteria and similar groups have also been detected on cave walls (Schabereiter-Gurtner et al, 2002;Ikner et al, 2007;Urzì et al, 2010). Cave walls, cave animals, insects and human visitors (Chelius & Moore, 2004;Portillo et al, 2009b) are therefore potential sources of bacterial species in cave sediments.…”
Section: Culture Independent and Dependent Surveymentioning
confidence: 99%
“…On the other hand, the genus Herbiconiux was only isolated from the KT. Several studies reported that Actinobacteria members cause biodeterioration of mural paintings in caves (Adetutu and Ball, 2014;Cuezva et al, 2012;Diaz-Herraiz et al, 2013;Urzì et al, 2010). The major taxa of actinobacterial colonizers in these caves belonged to the genera Streptomyces, Nocardia, and Pseudonocardia.…”
Section: -9mentioning
confidence: 99%
“…Other strains as for example Enterobacter hormaechei or Bacillus cereus displayed RISA profiles formed by three bands of different size. The RISA method was applied by previous authors for clustering the bacterial strains isolated from different environments (Pangallo et al 2004;Belgacem et al 2009;Urzi et al 2010), other kinds of DNA fingerprints methods were used in clustering the PAH degrading bacteria (La Rosa et al 2006;Abd-Elsalam et al 2009;Ruggeri et al 2009). …”
Section: Resultsmentioning
confidence: 99%